2015
DOI: 10.1111/jdv.13092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histopathological, dermatoscopic and digital microscopic features of dermatofibroma: a retrospective analysis of 200 lesions

Abstract: Background Dermatology literature lacks a study investigating both histopathological and dermatoscopic features of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
0
23
3
4
Order By: Relevance
“…Occasionally, dermatofibroma can also simulate normal skin on histology and may be positive for CD163. However, the histiocytic cells in dermatofibroma are larger with more abundant cytoplasm in comparison to the interstitial variant of GA where the mononuclear cells are small . In addition, dermatofibroma will be also positive for FXIIIa, which was negative in the small mononuclear cells in all of our cases of interstitial GA .…”
Section: Discussionmentioning
confidence: 56%
“…Occasionally, dermatofibroma can also simulate normal skin on histology and may be positive for CD163. However, the histiocytic cells in dermatofibroma are larger with more abundant cytoplasm in comparison to the interstitial variant of GA where the mononuclear cells are small . In addition, dermatofibroma will be also positive for FXIIIa, which was negative in the small mononuclear cells in all of our cases of interstitial GA .…”
Section: Discussionmentioning
confidence: 56%
“…Dermatoscopically we found that the most prevalent dermatoscopic feature was vascular structures (65%), followed by peripheral pigment network, contrasting with the general literature review which defines the most predominant finding as pigment network (Table ) . We attribute this to our dermatoscopic evaluation with polarized non‐contact dermatoscopy (PNCD), thus avoiding vascular compression and providing optimum imaging of the vascular structures.…”
Section: Discussionmentioning
confidence: 67%
“…Several types of DF have been identified dermatopathologically and with dermatoscopic correlation, the dermatopathology has been predictable in limited studies so far with some conclusions being drawn about the dermatopathological characteristics of DF from dermatoscopic clues.…”
Section: Introductionmentioning
confidence: 99%
“…Dermoscopy may enable differentiation of cellular neurothekeoma from other benign tumours such as dermatofibroma and neurofibroma. Dermoscopic patterns of typical dermatofibroma feature peripheral pigment network and a central, white scar‐like patch . The patterns of neurofibroma show peripheral pigmented network, peripheral halo of brown pigmentation and both pink‐red structureless and scar‐like areas .…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopic patterns of typical dermatofibroma feature peripheral pigment network and a central, white scar-like patch. 9 The patterns of neurofibroma show peripheral pigmented network, peripheral halo of brown pigmentation and both pink-red structureless and scar-like areas. 10 Although they sometimes demonstrate vascular patterns, arborising vessels are rare in both tumours.…”
Section: Discussionmentioning
confidence: 99%